Multidrug-resistant E. coli encoding high genetic diversity in carbohydrate metabolism genes displace commensal E. coli from the intestinal tract - Connor, Christopher H.; Zucoloto, Amanda Z.; Munnoch, John T.; Yu, Ian-Ling; Corander, Jukka; Hoskisson, Paul A.; McDonald, Braedon; McNally, Alan (PLOS Biology, 2023)
A mouse colonisation model reveals that a multidrug-resistant (MDR) strain of E. coli can displace commensal strains from the gut, and that unique selection pressures occurring in the MDR strain result in streamlining of their metabolism. Analysis of a curated set of 20,000 E. coli genomes shows that MDR lineages are associated with increased nucleotide sequence diversity in metabolism genes.